Human Failure: An analysis of 2000 incident reports - Williamson, J. A.; Webb, R. K.; Sellen, Abigail; Runciman, W. B.; Walt, J. H. Van Der (Anaesthesia & Intensive Care, 1993)
Information of relevance to human failure was extracted from the first 2,000 incidents reported to the Australian Incident Monitoring Study (AIMS). All reports were searched for human factors amongst the "factors contributing," "factors minimising", and "suggested corrective strategies" categories, and these were classified according to the type of human error with which they were associated. In 83% of the reports elements of human error were scored by reporters. "Knowledge-based errors" contributed directly to about one-quarter of incidents; the outcome of one third of incidents was thought to have been minimised by prior experience or awareness of the potential problems, and in one fifth some strategy to improve knowledge was suggested. Correction of "rule-based errors" or provision of protocols or algorithms were thought, together, to have a potential impact on nearly half of all incidents. Failure to check equipment or the patient contributed to nearly one-quarter of all incidents, and inadequate crisis management contributed to a further 1 in 8. "Skill-based errors" (slips and lapses) were directly responsible for 1 in 10 of all incidents, and were thought to make an indirect contribution in up to one quarter. "Technical errors" were responsible for about 1 in 8 incidents. Analysing the relative contribution of each type of error for each type of problem allows the development of rational preventative strategies.(